2018
DOI: 10.1111/cen.13860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and degree of insulin resistance in Chinese Han women with PCOS: Results from euglycemic‐hyperinsulinemic clamps

Abstract: 56.3% of Chinese Han women with PCOS had IR and their reduction in IS was 30.3%. Obesity exacerbated the reduction in IS. When being evaluated by HOMA, the prevalence and the risk factors of IR in Chinese women with PCOS were underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Similar to previous studies [21][22][23], in our study, about 69% of PCOS patients showed insulin resistance. In the analysis of risk factors, insulin resistance of PCOS patients is related to employment, the duration of disease, BMI, whether they take metformin at present, and the activity time.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies [21][22][23], in our study, about 69% of PCOS patients showed insulin resistance. In the analysis of risk factors, insulin resistance of PCOS patients is related to employment, the duration of disease, BMI, whether they take metformin at present, and the activity time.…”
Section: Discussionsupporting
confidence: 92%
“…Insulin resistance is a key aetiological feature in PCOS and underpins the metabolic dysfunction present in women with PCOS (Dunaif et al, 1989 ; Diamanti-Kandarakis and Papavassiliou, 2006 ). Although not currently included in the diagnostic criteria, insulin resistance determined from insulin clamps is prevalent in 56–95% of women with PCOS (Stepto et al, 2013 ; Tosi et al, 2017 ; Li et al, 2019 ). It is therefore important to understand the impact of exercise type and intensity and its interaction with diet to explore effective exercise interventions to alleviate insulin resistance in women with PCOS before major complications occur.…”
Section: Discussionmentioning
confidence: 99%
“…Global Burden of Disease studies have shown that the prevalence of obesity has doubled in 73 countries between 1980 and 2015 (Inoue et al, 2018). In addition, based on the 1990 National Institutes of Health standard, PCOS affects 6–10% of women worldwide (Goodarzi et al, 2011), and studies have indicated that 56.3% of Han women in China with PCOS have IR (Li et al, 2018). Therefore, in the face of such a large potential patient population, the harm caused by IR cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%